High-Intensity Focused Ultrasound Treatment in Refractory Glaucoma Patients: Results at 1 Year of Prospective Clinical Study. Issue 6 (December 2015) - Melamed, Shlomo; Goldenfeld, Modi; Cotlear, Daniel; Skaat, Alon; Moroz, Iris
Purpose: To evaluate the safety and efficacy of the ultrasonic circular cyclo-coagulation procedure using high-intensity focused ultrasound by a miniaturized annular device containing 6 piezoceramic transducers in patients with refractory glaucoma. Methods: This was a prospective interventional noncomparative study of 20 eyes of 20 patients with refractory glaucoma. All eyes were treated with 6 activated transducers operating at 21 MHz. Ultrasound biomicroscopy and a complete ophthalmic examination were performed before the procedure and at 1 day, 1 week, and 1, 3, 6, and 12 months after the procedure. Primary outcomes were surgical success (defined as intraocular pressure (IOP) reduction from baseline ≥20% and IOP >5 mm Hg) at the last follow-up visit. Secondary outcomes were mean IOP at each follow-up visit compared to baseline, medication use, complications, and re-interventions. Results: Intraocular pressure was significantly reduced (p<0.01) from a mean preoperative value of 36.4 ± 5.7 mm Hg to a mean postoperative value of 22.5 ± 10.3 mm Hg at 12 months. Four patients needed to be re-treated. The mean IOP reduction achieved was 38%. Surgical success was achieved in 13 of 20 eyes (65%). No major intraoperative or postoperative complications occurred. Conclusions: Ultrasonic circular cyclo-coagulation using high-intensity focused ultrasound delivered by a circular miniaturized device containing 6 piezoceramic transducers is an effective and well-tolerated method to reduce IOP in patients with refractory glaucoma.